Metal Oxide Mediated Extracellular NADPH Regeneration Improves Ethanol Production by Engineered Synechocystis sp. PCC 6803 - Velmurugan, Rajendran; Incharoensakdi, Aran (Frontiers in Bioengineering and Biotechnology, 2019)
The ethanol synthesis pathway engineered Synechocystis sp. PCC 6803 (hereafter Synechocystis) was used to investigate the influence of metal oxide mediated extracellular NADPH regeneration on ethanol synthesis. The in-vitro studies proved that the metal oxides have the potential to generate the NADPH in the presence of electron donor, the usual components of photoautotrophic growth conditions. When the NADPH regeneration was applied in Synechocystsis, the strain showed improved growth and ethanol production. This improved ethanol synthesis is attributed to the increased availability of NADPH to the ethanol synthesis pathway and redirection of closely related carbon metabolism into the ethanol synthesis. Under optimized light intensity and NADP addition, the maximum ethanol production of 5100 mg/L was observed in MgO mediated extracellular NADPH regeneration after 25 days of cultivation, which is 2-fold higher than the control. This study indicates the feasibility of metal oxide mediated extracellular NADPH regeneration of Synechocystis to increase the production of ethanol.